2022
DOI: 10.1007/s10072-022-06350-y
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic and neuropathic complaints of long-COVID objectified: an investigation from electrophysiological perspective

Abstract: Purpose Here , we aimed to assess the frequency and phenomenology of autonomic and neuropathic complaints of long-COVID and to evaluate them by means of electrophysiology. Methods Step 1. Patients with prior COVID-19 infection were screened by COMPASS-31 and mTORONTO to create the target population for further evaluation. Step 2. Patients with high scores were invited for a detailed history of their complaints and electrophysiological analysis, which included nerve cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 32 publications
2
10
0
Order By: Relevance
“…All studies included in this review reported that NCS, specifically sensory NCV, was not significantly affected when comparing healthy control to patients with COVID-19, which agrees with other studies that showed no or mild abnormalities in NCS ( 32 , 33 ). Also, patients initially referred for electrophysiological assessments due to sensory symptoms had abnormal MNCV, while the SNCV was generally normal ( 21 ).…”
Section: Discussionsupporting
confidence: 88%
“…All studies included in this review reported that NCS, specifically sensory NCV, was not significantly affected when comparing healthy control to patients with COVID-19, which agrees with other studies that showed no or mild abnormalities in NCS ( 32 , 33 ). Also, patients initially referred for electrophysiological assessments due to sensory symptoms had abnormal MNCV, while the SNCV was generally normal ( 21 ).…”
Section: Discussionsupporting
confidence: 88%
“…All of the studies included in this review reported that NCS findings, including sensory nerve conduction velocity (NCV), were not significantly altered in patients with COVID-19 relative to healthy controls. This aligns with previous research that revealed either no or very slight NCS abnormalities [7]. Studies of COVID-19 severity, considering factors such as intubation, weaning from mechanical ventilation, and pneumonia, have identified substantial variation in EMG/ NCS between more and less severe cases [8].…”
Section: ) Electromyography and Nerve Conduction Studiessupporting
confidence: 89%
“…We conducted a study with larger sample size as well. Another study by Ser et al revealed neuropathic and autonomic complaints in more than one-third of patients with long COVID-19 and abnormal cutaneous silent period suppression index but normal SSR parameters [ 29 ]. One of the reasons for the difference between the results of this study and our research could be that the SSR evaluation in the mentioned study was performed on a limited number of patients who had neuropathic or autonomic symptoms after COVID-19 infection (14 out of 38 cases).…”
Section: Discussionmentioning
confidence: 99%